Potential Diagnostic Applications of Multi-Delay Arterial Spin Labeling in Early Alzheimer’s Disease: The Chinese Imaging, Biomarkers, and Lifestyle Study - Sun, Mengfan; Wang, Yan-Li; Li, Runzhi; Jiang, Jiwei; Zhang, Yanling; Li, Wenyi; Zhang, Yuan; Jia, Ziyan; Chappell, Michael; Xu, Jun (Frontiers in Neuroscience, 2022)
Background: Cerebral blood flow (CBF) alterations are involved in the onset and progression of Alzheimer’s disease (AD) and can be a potential biomarker. However, CBF measured by single-delay arterial spin labeling (ASL) for discrimination of early AD was lack of accuracy. Multi-delay ASL can not only provide CBF quantification, but also provide arterial transit time (ATT). Unfortunately, the technique was scarcely applied to the diagnosis of AD. Here, we detected the utility of ASL with 1-delay and 7-delay in ten regions of interest (ROIs) to identify mild cognitive impairment (MCI) and AD. Materials and Methods: Pseudo-continuous ASL (pCASL) MRI was acquired on 3-T GE scanner in adults from Chinese Imaging, Biomarkers, and Lifestyle Study of Ageing Project (CIBL), including 26 normal cognition (NC), 37 MCI and 39 AD. Receiver operating characteristic (ROC) analyses with 1-delay and 7-delay ASL were performed for identification of MCI and AD. Results: For CBF of 1-delay or 7-delay the AUCs showed moderate-high performance for the AD/NC and AD/MCI comparisons (AUC = 0.83~0.96) (p < 0.001). CBF of 1-delay performed poorly in MCI/NC comparison (AUC = 0.69) (p < 0.001), but CBF of 7-delay fared well with an AUC of 0.79 (p < 0.001). The combination of CBF and ATT of 7-delay was more powerful for AD/NC, AD/MCI, MCI/NC comparisons with AUCs of 0.96, 0.89 and 0.89, respectively (p < 0.001). Futhermore, combination of CBF, ATT, sex, age, APOE ε4 and education improved further the accuracy (p < 0.001). Conclusion: The combination of CBF and ATT with 7-delay ASL showed high performance for identification of MCI and AD, indicating that it is a potential imaging biomarker in early AD.